Learning Heckscher-Ohlin Model in Five Easy Steps - GOKCEKUS, Omer; BENGYAK, Kevin (Journal of Economics and Political Economy, 2015)
Abstract. With students in the policy and business schools with no formal economics background in mind, we propose an intuitively appealing and simple step-by-step graphical approach to explain the Heckscher-Ohlin (HO) model. Our approach is simple because it needs only two pieces of information, specifically about factor endowments and factor intensities, and from there it uses straightforward logic to construct the HO model. In easy five steps we show how to build the HO model and derive its three theorems, specifically, pattern of trade, factor price equalization, and income distribution. Keywords. Heckscher-Ohlin theory, teaching economics. JEL. A20, F11